Analisis Daya Saing Dan Perubahan Struktural Karet Indonesia 2000-2010 - , Hotman Sidauruk ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Sometimes comodity policy handle by government not use economic tools, for example developing of one comodity should be concern of comparative advantage of that comodity compare to other country who produce the similar comodity too. One of Economic tools for comparing advantages is RSCA (Revealed Comparative Advantage (RSCA). Rubber as one of our superior comodity (viewed by source of income) from non oil and gas sector, still managed by government partially, which is shown by appointment of GAPKINDO as a body to act on behalf of Indonesia, except there are problem. Development progress og rubber comodity in fact there is no structural which is measured with IPS (Index Perubahan Structural). This fact express that rubber policy need more intensiveness attention from government. The two economic tools are used in this thesis research to proof that rubber comodity should be handled by government of the Republic Of Indonesia to grab more high value, economic escalation and farmer welfare as a specificly. Find that comparative advantage of rubber specifically natural rubber is very high, those are from 2000-2005 RSCA 0,93 increase to 0,94 in the year 2006, and 0,95 on 2007 , but 2008 decrease a little bit to 0,94 and stabil in 2009 on point 0,94 from maximum 1,00. This measerement shown that natural rubber comodity ha comparative advantage and categorized as one of three biggest RSCA beside pulp and textile that Indonesia has. From view of industrial tranformation, Indonesian rubber industri also not shown transformation, form primer to secondary, moreover to tertier sector. Indonesian rubber still stand on primer sector, and this is shown by IPS still dominated by natural rubber. On year 2000 amonut export of natural rubber is 97% and processing is 3%. On the contrary from 2004 to 2009 export of natural rubber increase to be 99% and processing rubber only 1%. This data shown that there is no transformation indexs With high RSCA and no transformation index, ruuber development policy wgich is now hold by Minitry Of Trade and Ministry Of Agriculture, GAPKINDO on behalf of Indonesia in tripartee cooperation with Malaysia and Thailand shoul be evaluated or refresh. Those condition above are weakness of rubber in one sides, but also opportunity in other sides. This situation motivates the writer to observe indonesian rubber condition on 2000-2010, besides expaectation of the global rubber market in the future are grown in accordance with economic escalation and increasing of awareness of environmental sustainability Malaysian and Thailand rubber production estimated should be decrease because the government policy to concentrated on the downstream sector and also divert part of the rubber area to palm oil area. Thailand and Malaysia also facing the limitation of area, which is located in the north side of Indonesia with marginal condition, so it means those area are less productivity than Indonesian area, also limitation avalability of labour Indonesia as a very potential country to develop the rubber comodity, because of higher RSCA especially in natural rubber, availability of land and labour, compatibility of climate and others should be make Indonesia grab this opportunity.